1994
DOI: 10.1104/pp.105.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Root Hair Deformation Activity of Nodulation Factors and Their Fate on Vicia sativa

Abstract: We used a semiquantitative root hair deformation assay for Vicia sativa (vetch) to study the activity of Rhizobium leguminosarum bv viciae nodulation (Nod) factors. Five to 10 min of Nod factor-root interaction appears to be sufficient to induce root hair deformation. The Rhizobium-legume interaction starts with the exchange of signal molecules between both partners. Flavonoids secreted by the roots of the host plant trigger the expression of the nodulation (nod) genes of Rhizobium, resulting in the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
211
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(220 citation statements)
references
References 22 publications
(39 reference statements)
7
211
1
1
Order By: Relevance
“…Studies on soybean have shown that if the NO 3 − treatment is delayed until 18 h after rhizobial inoculation its inhibitory effect is greatly diminished (Malik et al, 1987), indicating that in this species the earliest stages of nodulation are the most sensitive. In experiments with vetch (Vicia sativa) it was shown that to be effective at suppressing root hair deformation an NH 4 NO 3 treatment had to begin at least 24 h before the addition of the rhizobial Nod factor (which is able to initiate the process of root hair curling) (Heidstra et al, 1994). The finding that the root hairs had to develop in the presence of NH 4 NO 3 for its effect to be seen, suggested that the NH 4 NO 3 treatment might be interfering with perception or transduction of the Nod factor signal or that that the NH 4 NO 3 somehow alters the development of the root hairs so that they are unable to curl (Heidstra et al, 1994).…”
Section: Nodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on soybean have shown that if the NO 3 − treatment is delayed until 18 h after rhizobial inoculation its inhibitory effect is greatly diminished (Malik et al, 1987), indicating that in this species the earliest stages of nodulation are the most sensitive. In experiments with vetch (Vicia sativa) it was shown that to be effective at suppressing root hair deformation an NH 4 NO 3 treatment had to begin at least 24 h before the addition of the rhizobial Nod factor (which is able to initiate the process of root hair curling) (Heidstra et al, 1994). The finding that the root hairs had to develop in the presence of NH 4 NO 3 for its effect to be seen, suggested that the NH 4 NO 3 treatment might be interfering with perception or transduction of the Nod factor signal or that that the NH 4 NO 3 somehow alters the development of the root hairs so that they are unable to curl (Heidstra et al, 1994).…”
Section: Nodulationmentioning
confidence: 99%
“…In experiments with vetch (Vicia sativa) it was shown that to be effective at suppressing root hair deformation an NH 4 NO 3 treatment had to begin at least 24 h before the addition of the rhizobial Nod factor (which is able to initiate the process of root hair curling) (Heidstra et al, 1994). The finding that the root hairs had to develop in the presence of NH 4 NO 3 for its effect to be seen, suggested that the NH 4 NO 3 treatment might be interfering with perception or transduction of the Nod factor signal or that that the NH 4 NO 3 somehow alters the development of the root hairs so that they are unable to curl (Heidstra et al, 1994). The former possibility was eliminated when the NH 4 NO 3 treatment was shown not to block induction by the Nod factor of the VsLb1 gene, which is one of the earliest events in the root hair's response to rhizobial infection (Heidstra et al, 1997).…”
Section: Nodulationmentioning
confidence: 99%
“…The root hair infection process is intimately associated with the reorientation of polarized tip growth of root hairs in the susceptible root zone close to the root tip. The root hairs of the infection zone exhibit altered growth behavior, called root hair deformation or root hair curling (Heidstra et al, 1994). Root hair deformation is the result of isotropic growth, by which the tip of the hair swells and then grows in an altered direction (Esseling et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nod factors are responsible for the induction of a series of responses in the host, such as depolarization of the root hair plasma membrane (Ehrhardt et al, 1992;Felle et al, 1995;Kurkdjian, 1995), alkalinization of root hair cells (Felle et al, 1996), oscillation of the free cytoplasmic calcium concentration in root hairs (Ehrhardt et al, 1996), induction of root hair deformation (Lerouge et al, 1990;Spaink et al, 1991;Heidstra et al, 1994), induction of early nodulin (ENOD) genes (Horvath et al, 1993;Journet et al, 1994), and mitotic reactivation of cortical cells (Spaink et al, 1991). The latter is the beginning of the formation of primordia which, upon infection by rhizobia, develop into root nodules.…”
mentioning
confidence: 99%